Tibial fracture correction, rehabilitation, and release of a Jaguarundi (Herpailurus yagouaroundi) in Costa Rica - Jimenez-Soto, Mauricio (2024)
This paper describes the medical-surgical approach, rehabilitation, and release of a Herpailurus yagouaroundi suffering from a comminuted fracture to the distal third of the left tibia. The tibial fracture was the result of vehicular trauma that occurred on a main highway within a biological corridor in the northern region of Costa Rica. The feline was rescued by officials from the Costa Rican National System of Conservation Areas (SINAC) and was treated at the Small Animals and Wildlife Hospital (HEMS) of the School of Veterinary Medicine (EMV) from the National University of Costa Rica (UNA). The medical-surgical approach included homeostatic restoration of the patient, collateral tests (laboratory test and diagnostic images) and correction of the tibial fracture using an external skeletal fixator with titanium bars and anchors. The patient received post-operative care and rehabilitation before a successful release into its natural habitat.